2015
DOI: 10.1007/s00393-014-1559-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of aquatic exercise for treatment of knee osteoarthritis

Abstract: Aquatic exercise appears to have considerable short-term benefits compared with land-based exercise and nonexercise in patients with knee OA. Based on these results, aquatic exercise is effective and safe and can be considered as an adjuvant treatment for patients with knee OA. Studies in this area are still too scarce and too short-term to provide further recommendations on how to apply this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 46 publications
4
40
1
6
Order By: Relevance
“…buoyancy, which decreases loading of joints, and finally the unique characteristics of water-based exercising which may allow people to perform exercises which otherwise they would be unable to perform on land. The findings of some of the studies in the field including Alcalde et al (2017), Taglietti et al (2018), and Lu et al (2015) are in line with our findings [18,19,25]. Consistent with the results of the present study, they reported that aquatic exercises could improve pain, function, and balance in patients with KOA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…buoyancy, which decreases loading of joints, and finally the unique characteristics of water-based exercising which may allow people to perform exercises which otherwise they would be unable to perform on land. The findings of some of the studies in the field including Alcalde et al (2017), Taglietti et al (2018), and Lu et al (2015) are in line with our findings [18,19,25]. Consistent with the results of the present study, they reported that aquatic exercises could improve pain, function, and balance in patients with KOA.…”
Section: Discussionsupporting
confidence: 93%
“…To add more, some studies have patients. They concluded that aquatic exercise was effective and safe enough to be considered as an adjuvant treatment for patients with knee OA [18,19]. Knee proprioception improvement has also been reported in patients with knee osteoarthritis following aquatic exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Since osteoarthritis can be a barrier to physical activity (52), water-based physical activities, such as swimming, walking or running in a pool, or aquatic fitness classes have been encouraged for people with such comorbidities (53,54). While few highquality trials exist, a recent meta-analysis suggests aquatic exercise improves A1C compared to no exercise comparison groups and that the improvements are comparable to those obtained with landbased exercise (55).…”
Section: Benefits Of Other Types Of Exercisementioning
confidence: 99%
“…compared with land-based exercise, evidence from meta-analyses of six studies (five with a risk of selection bias due to poor reporting of allocation of concealment; 398 participants) suggested that AT produces similar improvements in self-reported pain and function (Lu et al, 2015). However, the longer-term effects of AT are not clear (Cochrane, Davey, & Matthes Edwards, 2005;Lund et al, 2008).…”
mentioning
confidence: 99%